The challenges in providing rehabilitation for children with complex needs. (September 2013) - Barker, Roz; Bathgate, Fionna
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents issues to consider when creating an appropriate cochlear implant rehabilitation package for children with complex needs. Factors associated with audiological, communication, and psychosocial issues are considered along with the impact on a typical cochlear implant service. The importance of a Multi-disciplinary Team (Audiology, Psychology, Speech & Language Therapy, Teacher of the Deaf) input to rehabilitation and the need to identify appropriate 'Red Flags' and outcome measures for this specific population are also considered.